Kondisi Kesehatan Kulit Mahasiswa yang Mengosumsi Makanan Instan - Sarah Aulia; Ratih Aniska Sihombing; Putri Anissa Hutasoit; Utami Nurhafsari Putri (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The rising consumption of instant foods among university students has become a prominent trend influenced by academic pressure, limited time, economic constraints, and modern fast-paced lifestyles. This literature-based study aims to analyze the relationship between instant food consumption and skin condition, particularly acne vulgaris, among students. Findings from previous research indicate that high-glycemic foods, saturated fats, sodium, and food additives commonly found in instant products contribute to systemic inflammation and may trigger acne development. Moreover, an imbalanced nutrient intake resulting from frequent instant food consumption may negatively impact overall skin health, including hydration, elasticity, and cellular regeneration. In contrast, cooking activities have been shown to promote psychological well-being, mindfulness, and healthier food choices. By synthesizing current empirical evidence, this study highlights how dietary patterns play a significant role in shaping students' skin conditions. The results are expected to serve as a valuable reference for students, educational institutions, and food industries in promoting healthier eating behaviors.